Exploring microRNAs, Target mRNAs and their Functions in Leguminous Plant Arachis hypogaea - Rajendiran, Anjana; Vijayakumar, Saravanan; Pan, Archana (MicroRNA, 2019)
Background: MicroRNAs (miRNAs) are a class of small non-coding, endogenous RNAs that regulate gene expression at post-transcriptional level. In plants, miRNAs are usually of 18-24 nucleotide in length and play humongous role by aiding in development, growth, defense, biotic and abiotic stress responses, etc. Objective: Arachis hypogaea is an economically important oil seed crop and human dietary source cultivated mostly in tropical and subtropical regions. In the present study, an initiative was taken to uncover miRNAs, their targets and functions in this important plant species. Method: Comparative genomics strategy coupled with bioinformatics approaches was deployed for the identification of miRNAs, their corresponding targets and functions by exploiting biological databases and tools. Results: The study was able to identify 34 conserved miRNA candidates, belonging to 17 miRNA families, contributed by 23 and 3 precursor miRNAs from A. hypogaea Expressed Sequence Tags (EST) and Genome Survey Sequences (GSS), respectively. As well, 495 EST and 917 unigene sequences were predicted as targets for the identified miRNAs. Herein, psRNAtarget server and TargetFinder tool were used to predict unigene targets, whereas comparative genomics strategy was used for identifying EST targets. Functional annotation of the identified targets revealed that the identified miRNAs regulate mRNAs that participate in key biological and metabolic processes. Pathway enrichment analysis using KEGG database also revealed that they regulate important metabolic pathways including antibiotic biosynthesis, biosynthesis of unsaturated fatty acids, amino acids metabolism and flavonoid biosynthesis. Conclusion: The outcome of the study would aid experimental biologists to focus on these miRNAs to facilitate improved crop development and yield.
Keywords: Arachis hypogaea